Determinating the STEM Education Compentencies of Pre-Service Teachers - Dilber Acar; Yasemin Büyükşahin; Tuğba Ecevit (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
With solely academic knowledge, it appears challenging for today's students to find a place for themselves in the business world where they will operate in the future. Therefore, it is crucial to provide students with a variety of abilities, such as problem-solving, critical thinking, creativity, collaboration, and analytical thinking, in addition to academic knowledge. The STEM education approach is one of the approaches that aims to equip students with the knowledge and abilities they need in the fields of science, technology, engineering, and mathematics while also educating them as persons with 21st-century competencies. In this context, it is the teachers who will provide students with these knowledge and skills and apply STEM education. In this sense, it is thought that teachers' knowledge and competencies in STEM teaching are significant. In this study, it was aimed to determine the STEM teaching competencies of pre-service teachers studying in the last year of education faculties. The case study design, one of the qualitative research methods, was used in the research. The study group of the research consists of 45 final year science and classroom teaching students studying at 21 different universities in Turkey. The data of the research was obtained by the "STEM Teaching Competencies Questionnaire" developed by the researchers. The obtained data were analyzed simultaneously by three different researchers using content analysis. During the analysis process, codes, categories and themes were created. As a result, it can be claimed that pre-service teachers have theoretical knowledge of STEM education, but they do not think of themselves as highly competent. They require more hands-on education and wish to use it when they begin their careers, but they need practice-based education for this